2015
DOI: 10.12983/ijsrk-2015-p0181-0186
|View full text |Cite
|
Sign up to set email alerts
|

Eye Color Pattern During Isolation Indicates Stress-Coping Style in Nile Tilapia Oreochromis niloticus L.

Abstract: Abstract. It has previously been shown that changes in eye color pattern (ECP) in Oreochromis niloticus is a consequence of a fish's relative position in the social hierarchy. However, it is still an open question if ECP during isolation is correlated to stress coping styles in fish such as ventilation rate (VR). To evaluate this, 94 all-male juvenile O. niloticus of similar size were introduced in a novel environment and were isolated in aquaria for 7 days. The ECP and VR of each fish were recorded daily duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Melanocyte-stimulating hormone (α-MSH) and melanin-concentrating hormone (MCH) are the two main hormones involved in the modulation of chromatophore dispersal [68–71], and it has been shown that social stress can increase α-MSH in plasma and result in body darkening in salmonids [72,73]. Eye and body darkening are associated with subordinance [41,74] and a reactive coping style in Nile tilapia [42], as found in our study. Thus, our results are consistent with the idea that crowding during aquaculture intensification makes Nile tilapia chronically stressed, and as seen in other species, this results in body and eye darkening, neophobia and, more generally, in a shift from a proactive to a reactive stress coping style.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanocyte-stimulating hormone (α-MSH) and melanin-concentrating hormone (MCH) are the two main hormones involved in the modulation of chromatophore dispersal [68–71], and it has been shown that social stress can increase α-MSH in plasma and result in body darkening in salmonids [72,73]. Eye and body darkening are associated with subordinance [41,74] and a reactive coping style in Nile tilapia [42], as found in our study. Thus, our results are consistent with the idea that crowding during aquaculture intensification makes Nile tilapia chronically stressed, and as seen in other species, this results in body and eye darkening, neophobia and, more generally, in a shift from a proactive to a reactive stress coping style.…”
Section: Discussionmentioning
confidence: 99%
“…Tilapias rank among the oldest and most widely farmed fish worldwide [19,36], but are also included in the ‘100 world's worst invasive alien species' [40], so knowledge about how these species respond to novelty when they escape from fish farms and become feral might be important for reducing impacts. To address these questions, we reared juvenile Nile tilapia at high and low densities, measured the extent of eye and skin darkening (two metrics of chronic stress, [41,42]), and screened them for neophobia, as well as for activity, aggression and boldness, as these are measures of stress coping style [43,44]. We used fry because this allowed us to address the effect of rearing density at a critical stage of development, when the young leave the care of their parents and variation in exploratory behaviour is first manifested [45].…”
Section: Introductionmentioning
confidence: 99%
“…For ECP, it was quantified as a darkened area of both the iris and sclera. The circular area of the eye was divided into 8 equal parts using an imaginary diameter line and the ECP value that was observed ranged from zero (no darkening) to eight (total darkening) (based on Volpato et al, 2003;Vera Cruz and Tauli, 2015).…”
Section: Monitoring Of Ventilation Rate Eye Color Pattern and Skin mentioning
confidence: 99%
“…This happened when the fish sensed a change in their environment. The eye color may also indicate the level of stress; with more stress as the color became darker (Vera Cruz and Tauli, 2015).…”
Section: Eye Color Patternmentioning
confidence: 99%
See 1 more Smart Citation